Herbal medicine: a survey of use in Nigerian presurgical patients booked for ambulatory anaesthesia - Onyeka Tonia C; Ezike Humphrey A; Nwoke Ogochukwu M; Onyia Emeka A; Onuorah Elias C; Anya Samson U; Nnacheta Timothy E (BMC, 2012)
Abstract Background Utilization of herbal medicines in the preoperative period by Nigerian patients booked for day case surgery has not been explored. Methods Cross-sectional survey of 60 patients presenting for day-case surgery at a tertiary healthcare institution over a 3-week period in August 2011 was conducted. Using a structured questionnaire, inquiries were made concerning use of herbal medicines in the immediate preoperative period. Socio-demographic characteristics, information on use of concurrent medical prescriptions, types of herbs used, reasons for use, perceived side effects and perceived efficacy were obtained. Data were evaluated using descriptive statistics and Chi-square. Results Fifty-two (86.7%) were American Society of Anesthesiologists (ASA) class 1 while 8 (13%) were ASA 2. Most patients (86.7%) had their procedures done under local infiltration with monitored anaesthesia care (MAC), while 5.0% and 8.3% had their procedures done under regional and general anaesthesia, respectively. About 48.3% of respondents were on concurrent medical prescriptions while 51.7% were not. Forty percent (40%) of patients admitted to use of herbal medicine, all by the oral route, in the immediate perioperative period; 87.5% did not inform their doctor of their herbal use. Types of herbs used included 'dogonyaro', 'agbo', 'nchanwu', and Tahitian noni. Treatment of malaria was commonest reason for use in 29.2% of patients, while cough and concurrent surgical condition were reasons given by 12.5% of patients, respectively. Seventy-nine percent (79.2%) of patients considered their herbal medications effective. Perceived side effects of herbal medication (16.6%) included fever, waist pain and intoxication. There were no variations in use between ASA 1 and ASA 2 patients and none between respondents on conventional medication against those that were not. Variables such as age less than 35 years, female gender, being married and being an urban dweller did not show any significant difference in use. Conclusion This survey revealed many patients were on one or more herbal preparations in the immediate preoperative period. In consideration of possible untoward drug interactions between conventional medication, herbal preparations and anaesthesia, doctors (especially anaesthetists) should routinely assess all patients booked to be anaesthetized, especially those for day case surgery. The authors recommend surveys with larger respondent numbers to determine prevalence of use and possible interactions between indigenous Nigerian herbs and anaesthesia.